Consideration of partial discharge energy in a mathematical model of thermal-fluctuation processes of a power cable - Dubyago, M. N.; Polyuyanovich, N. K.; Burkov, D. V. (EAI Endorsed Transactions on Energy Web, 2019)
The article shows that the presence of impurities or oxidation products resulting from heating in insulation leads to leakage currents. A mathematical model was obtained that allows calculating the power of partial discharges (PD), as well as determining the location of the m1 inclusion in the main insulation, due to the power of the active component of the leakage current, when it occurs in the main cable insulation. The calculation of the change in heat flux passing through the layers of cable insulation by the piecewise-specified functions method, taking into account the thermal resistance of the inclusion, is carried out. The method proposed in the developed model makes it possible to account for heat losses based on the thermal and geometric dimensions of the inclusion. This will allow to obtain the temperature in all layers of the PCL, starting from the radial distances, inclusion parameters caused by the insulation core current, as the main temperature-forming factor.